Love and respect [the love she most desires, the respect he desperately needs] - Eggerichs, Emerson (Carol Stream, IL : Oasis Audio, 2004)
Using extensive biblical and scientific research, Dr. Emerson Eggerichs reveals the secret to couples meeting each other's deepest needs: without love she reacts without respect, and without respect he reacts without love and a destructive, vicious cycle begins. Eggerich offers help to husbands and wives, introducing the biblical teaching of unconditional respect, and explaining why it is as powerful as unconditional love.
Includes references
Abridged.
Compact discs.
Read by the author.
Keywords: Spouses -- Religious life; Love -- Religious aspects -- Christianity; Respect -- Religious aspects -- Christianity